54 The geographical distribution of colorectal polyps in the west of ireland population. (5th April 2017) - Storan, D; Slattery, E
Abstract : Background: BowelScreen, the faecal immunochemical test based national colorectal cancer screening programme, commenced in May 2013. There is a large variation in the global distribution of colorectal cancer, but there is limited data on local geographic variations. Aim: The primary aim was to investigate for local variations in geographic distribution of colorectal polyps in the UHG BowelScreen catchment area. Method: All screening colonoscopies completed were analysed for the presence of advanced pathology (i.e. polyp ≥10 mm and/or ≥5 polyps detected and/or tumour detected). Only towns with a population ≥1000 as per 2011 census figures were included. Results: Between 2013 and 2016; 1191 colonoscopies were included, with 790 patients having a polyp detected (67% of the total cohort) of whom 295 (25%) found to have advanced pathology. 153/1191 (13%) had polyps>10 mm in size, 153/1191 (13%) had ≥5 polyps and 32/1191 (3%) had tumours diagnosed based on endoscopic appearance. The prevalence of large polyps ranged from 3.2-32/10, 000 per settlement. Similar trends were seen with respect to multiple polyps (from 0-23/10, 000) and cancer (0-5/10, 000). Hotspots of advanced findings were particularly notable in east Galway (Ballinasloe, Tuam, Loughrea) and mid Mayo (Swinford, Ballyhaunis, Belmullet). Conclusions: There appears to be a wide local variation in the local geographic distribution of advanced colorectal polyps. This variation may be due to a combination of demographic, lifestyle, environmental or genetic differences in each area. Further study is needed, and could identify areas where bowel screen advertising could be intensified to improve participation rates and yields of endoscopy.